Kajian Praklinis Ekstrak Etanol Herba Tridax procumbens (Linn.) sebagai Antidiabetik pada Tikus Putih Diabetes (Rattus norvegicus) yang Diinduksi Streptozotosin: Preclinical Study of Ethanol Extract of Herba Tridax procumbens (Linn.) as Antidiabetic in Streptozotocin-Induced Diabetic White Rats (Rattus norvegicus) - Syaiful Katadi; Irman Idrus; Arman Rusman; Sitti Sarfila (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2023)
This study aims to conduct a preclinical study of the antidiabetic effect of the ethanol extract of the herb Tridax procumbens (Asteraceae) in streptozotocin-induced diabetic rats. The research procedure began by collecting test samples of the Tridax procumbens Linn (TP) herb. All parts of the TP plant which were air-dried were extracted with ethanol (95%) by maceration for 72 hours, then phytochemical screening was carried out to determine the content of secondary metabolites in general. The antidiabetic test was initiated by inducing male Wistar rats with streptozotocin (50 mg/jk, i.p.) and nicotinamide (120 mg/kg, i.p.) by injection. Diabetic rats were treated with glibenclamide (0.25 mg/kg, po) and TP extract (250 and 500 mg/kg, p.o.) for 21 consecutive days. Blood samples were collected periodically to measure the hypoglycemic effect of the TP extract. Then, variations in body weight at the fair were monitored for all experimental animals. The results showed that TP extract had a significant antidiabetic effect on diabetic white rats (Rattus norvegicus), with the best results given TP extract at a dose of 500 mg/kg. Keywords: Tridax procumbens, diabetes mellitus, antidiabetic Abstrak Penelitian ini bertujuan untuk melakukan kajian praklinis efek antidiabetes dari ekstrak etanol herba Tridax procumbens (Asteraceae) pada tikus diabetes yang diinduksi streptozotocin. Prosedur penelitian dimulai dengan mengumpulkan sampel uji herba Tridax procumbens Linn (TP). Seluruh bagian tanaman TP yang telah dikeringkan diekstraksi dengan etanol (95%) dengan cara dimaserasi selama 72 jam, selanjutnya dilakukan skrining fitokimia untuk mengetahui kandungan metabolit sekundernya secara umum. Untuk Uji antidiabetes dimulai dengan menginduksi tikus Wistar jantan dengan streptozotocin (50 mg/kg, ip) dan nicotinamide (120 mg/kg, ip). Tikus diabetes diobati dengan glibenklamid (0,25 mg/kg, po) dan ekstrak TP (250 dan 500 mg/kg, p.o.) selama 21 hari berturut-turut. Sampel darah dikumpulkan secara berkala untuk mengukur efek hipoglikemik ektrak TP. Kemudian, variasi berat badan mingguan dipantau untuk semua hewan percobaan. Hasil penelitian menunjukkan ekstrak TP memiliki efek antidiabetik yang signifikan terhadap tikus putih diabetes (Rattus norvegicus), dengan hasil terbaik pada pemberian ekstrak TP dosis 500 mg/KgBB. Kata Kunci: Tridax procumbens, diabetes mellitus, antidiabetik